Upaya Memperkuat Desa: Suatu Implementasi Kebijakan Pengangkatan Tenaga Kontrak Daerah Di Kabupaten Halmahera Utara - simson tondo; Bonny Datty (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
The effort to strengthen the village is the constitutional mandate contained in Law Number 6 of 2014 concerning Villages. the law is considered to place the village government as the subject of development in the village, has broad autonomy, and has broad authority in regulating governance in accordance with the potential of each village. On the other hand, there are concerns from the village government because they do not have the ability to carry out the village law mandate. Responding to village worries in North Halmahera, a North Halmahera Regent Decree was born numbered 814.1 / 2018 concerning Appointment of Regional Contract Workers with Work Agreements in Villages in North Halmahera Regency. This study aims to analyze the implementation of the policy for the appointment of regional contract workers in an effort to strengthen villages in North Halmahera Regency. Furthermore, this study uses qualitative research methods. Because of this the unit of analysis of this research is the village government of the Central Tobelo sub-district and the results of this study indicate that the Regional Government Policy of the North Halmahera Regency in the appointment of regional contract workers did not run smoothly in accordance with the program's objectives, due to lack of communication or direct socialization to the village government or community. Most of the contract workers assigned in the villages cannot carry out their main tasks, because of their limited capacity and because they are not given assignments by the local village government. As for funding this program, there is no problem, all regional contract workers are paid above the district minimum wage standard. In the implementation of regional contract personnel recruitment has been carried out openly and transparently. Furthermore, there is no good collaboration between the Regional Personnel Agency and Apparatus Resources with the Community and Village Empowerment Agency in coaching and training so that contract workers cannot carry out their duties properly.